Isolated Superior Oblique Muscle Swelling Causing Acute Vertical Strabismus in Graves’ Disease - Keiichi Aomatsu; Shunji Kusaka (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of isolated superior oblique muscle swelling causing acute vertical strabismus in Graves’ disease. Case. A 26-year-old woman with a 1-month history of misalignment of the right eye and diplopia was referred to us. Her visual acuity and intraocular pressures were normal in both eyes, but eye movement tests showed clear misalignment of her right eye. Antibody tests for myasthenia gravis were negative. However, blood tests revealed abnormal levels of thyroid-related factors, such as decreased thyroid-stimulating hormone, elevated free T3 and T4, and elevated anti-thyroid-stimulating hormone receptor antibody. We performed magnetic resonance imaging (MRI), which showed slight enlargement of the left superior oblique muscle. The patient was eventually diagnosed with Graves’ disease with superior oblique muscle involvement and underwent a thyroidectomy. Three months postoperatively, her diplopia and abnormal eye movements had substantially resolved. Conclusion. Isolated superior oblique muscle involvement may be a presenting symptom of Graves’ disease. It should be taken into consideration that, in the early stages of thyroid-associated ophthalmopathy (TAO) in adults, only the superior oblique muscle may be enlarged.